Pengaruh Suku Bunga dan Inflasi terhadap Profitabilitas pada Perusahaan Sektor Properti dan Real Estat yang Terdaftar di Bursa Efek Indonesia (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to determine the effect of interest rates and inflation on the profitability of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024. Profitability is measured using the Return on Assets (ROA) ratio, while interest rates refer to the BI-7 Day Reverse Repo Rate and inflation is calculated based on the Consumer Price Index (CPI) data from Bank Indonesia. This study uses a quantitative approach with multiple linear regression analysis methods and classical assumption tests supported by data processing using SPSS version 27 software. The sample was selected using purposive sampling techniques with criteria of companies that consistently submit annual financial reports, do not record losses during the research period, and use the Rupiah currency. The research results indicate that partially, interest rates have a positive and significant effect on profitability, while inflation does not have a significant effect on profitability. However, simultaneously, interest rates and inflation together have a significant effect on the company's profitability. These findings are expected to serve as a strategic reference for companies in formulating financial policies to maintain profitability stability amidst macroeconomic dynamics.